Engaging with Bediuzzaman Said Nursi : a model of interfaith dialogue - Markham, Ian S. (Farnham, Surrey, England ; Burlington, VT : Ashgate, 2009)
"Too often interfaith dialogue is generic and unfocused. Often it involves 'liberals' from each tradition coming together to criticize the 'conservatives' in their own traditions. This book provides a model for interfaith dialogue that challenges very directly the 'dialogue industry'." "This book involves a Christian theologian in deep conversation with a Muslim theologian. In the first eight chapters of this book, we engage closely with the thought of Nursi and tease out insights that Christians can learn from and accommodate." "Having established the method, the second section of the book examines the precise implications for the interfaith movement. Moving out from Islam, the book then demonstrates how the model of interfaith changes when Christians are in conversation with Hinduism in India. A new set of Dialogue Ten Commandments are suggested. The book concludes with an appeal for a commitment to include and reach the 'conservatives' in the major religious traditions."--BOOK JACKET.
Part one : learning from Said Nursi. Introduction : Christian theology and Islam -- Religious basis for ethics -- Challenging atheism -- Living life accountable -- Faith first, politics second -- Engaging religious diversity -- Coping with globalization -- Grounded spirituality : the challenge of Bediuzzaman Said Nursi -- What Christians can learn from Bediuzzaman Said Nursi -- Part two : rethinking dialogue. The dialogue industry -- Learning from India -- A new decalogue -- Conservatives and dialogue : why it is essential to get conservatives excited about the dialogue project -- Neither conservative nor liberal : a theology of Christian engagement with non-Christian traditions -- Conclusion.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Nursi, Said, -- 1873-1960.; Christianity and other religions -- Islam; Islam -- Relations -- Christianity; Dialogue -- Religious aspects -- Christianity; Dialogue -- Religious aspects -- Islam; Nurculuk; Electronic books